Gen Z's Passion for Apparel Products in East Kalimantan, Indonesia - Andansari, Dita; Shyafary, Darius; Bhakti, Sektalonir Oscarini Wati (Poltanesa, 2024)
Gen Z has different characteristics from previous generations, such as millennial, Generation X  as well as baby boomers. In addition to having a negative side where Gen Z does not have the strength to survive in his work, it also has several good characteristics including having financial literacy knowledge, having independence, having an understanding of Pancasila values, maintaining local culture, developing quality in the face of global competition in the 5.0 era., generation Z in Indonesia which is considered to uphold a collectivist culture, happiness is closely associated with the achievement of goals, happiness felt by relatives, especially with parents. With the demographic bonus and the potential possessed by Gen Z, it is also necessary to know what order is purchased by Gen Z to meet his needs so that it can be used as a reference to take business or business opportunities. Fashion products are included in the category of products most purchased by Gen Z, which is 37.40%. It is necessary to see how Gen Z chooses fashion products, especially in choosing the right bags. The method used in this study was a qualitative descriptive method. From the results of the analysis, it was found that Gen Z in choosing sling bags and tote bags was different in terms of emotional appeal, design and function. The design of the sling bag has many decorations, it gives less pride and is less comfortable to carry things. Tote bags provide their own versatility, simple design and strong enough to carry goods.